Latte Rebellion - Stevenson, Sarah Jamila (N.Y. Scholastic, 2011)
When high school senior Asha Jamison is called a "towel head" at a pool party, she and her best friend Carey start a club to raise awareness of mixed-race students that soon sweeps the country, but the hubbub puts her Ivy League dreams, friendship, and beliefs to the test.
Keywords: Clubs; Racially mixed people; Racism; High schools; Schools; East Indian Americans; Family life -- California; California